2017
DOI: 10.1038/ncb3513
|View full text |Cite
|
Sign up to set email alerts
|

The EMT-activator Zeb1 is a key factor for cell plasticity and promotes metastasis in pancreatic cancer

Abstract: Metastasis is the major cause of cancer-associated death. Partial activation of the epithelial-to-mesenchymal transition program (partial EMT) was considered a major driver of tumour progression from initiation to metastasis. However, the role of EMT in promoting metastasis has recently been challenged, in particular concerning effects of the Snail and Twist EMT transcription factors (EMT-TFs) in pancreatic cancer. In contrast, we show here that in the same pancreatic cancer model, driven by Pdx1-cre-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
726
1
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 824 publications
(766 citation statements)
references
References 73 publications
36
726
1
3
Order By: Relevance
“…Expanding and differential roles of ZEB1 and ZEB2 have been identified in various types of cancers in recent years (Chaffer et al ., 2013; Krebs et al ., 2017; Mejlvang et al ., 2007; Morel et al ., 2017; Si et al ., 2015; Spaderna et al ., 2008). ZEB1 is expressed primarily in nonepithelial cells, and a genome‐wide analysis of ZEB1‐binding regions performed in an adipogenesis model clearly shows its physiological importance (Gubelmann et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Expanding and differential roles of ZEB1 and ZEB2 have been identified in various types of cancers in recent years (Chaffer et al ., 2013; Krebs et al ., 2017; Mejlvang et al ., 2007; Morel et al ., 2017; Si et al ., 2015; Spaderna et al ., 2008). ZEB1 is expressed primarily in nonepithelial cells, and a genome‐wide analysis of ZEB1‐binding regions performed in an adipogenesis model clearly shows its physiological importance (Gubelmann et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…EMT is activated by several transcription factor families (ZEB, SNAIL, TWIST, FOXO, and others) (7). In a pancreatic cancer model driven by PDX1-Cre-mediated activation of mutant Kras and p53 alleles, multiple EMT-activating transcription factors (EMT-TFs) are upregulated, and metastasis is ablated by inactivation of ZEB1 but not SNAIL or TWIST (8,9), suggesting variable prometastatic activities. In breast and lung adenocarcinomas, high ZEB1 expression levels confer tumor-initiating and metastatic activities and are correlated with a poor prognosis (10).…”
Section: Introductionmentioning
confidence: 99%
“…The epithelial-to-mesenchymal transition activator ZEB1 initiates a prometastatic competing endogenous RNA network Xiaochao 5 Ali Jalali, 6 Milind Suraokar, 7 Junya Fujimoto, 7 Carmen Behrens, 1,7 Xiuping Liu, 8 Chang-gong Liu, of the 6 miRs, we used a prediction algorithm (www.targetscan. org) to query RNA-Seq data from 393P_ZEB1 cells and 393P_ vector cells and found that the genes upregulated at least 2-fold by ectopic ZEB1 expression were enriched in predicted targets of 5 miRs ( Figure 1B).…”
Section: Introductionmentioning
confidence: 99%
“…We have strong indications that in the absence of Zeb1 EMT is blocked, cell plasticity is impaired in multiple ways and colonization capacities are largely reduced, 5 however, it cannot be excluded that alternative mechanisms exist in vivo to induce EMT. Zeb1-deficient tumor cells may have found a loophole for metastasis formation via the remaining EMT-TFs expressed at low levels.…”
mentioning
confidence: 99%
“…Our data indicate that Zeb1 provides cellular plasticity, a prerequisite to escape the primary tumor mass and to adapt to the novel and hostile environment on the way to metastatic colony formation. 5 Isolated and cultured tumor cell lines specifically lost their colonization capacity in the absence of Zeb1. However, the effect of Zeb1 on tumor cell dissemination and survival in the blood stream still has to be analyzed thoroughly during disease progression in the genetic mouse tumor model.…”
mentioning
confidence: 99%